SARS-CoV-2 spike protein co-opts VEGF-A/neuropilin-1 receptor signaling to induce analgesia. Issue 1 (January 2021) - Moutal, Aubin; Martin, Laurent F.; Boinon, Lisa; Gomez, Kimberly; Ran, Dongzhi; Zhou, Yuan; Stratton, Harrison J.; Cai, Song; Luo, Shizhen; Gonzalez, Kerry Beth; Perez-Miller, Samantha; Patwardhan, Amol; et al.
Abstract : Abstract: Global spread of severe acute respiratory syndrome coronavirus 2 continues unabated. Binding of severe acute respiratory syndrome coronavirus 2's spike protein to host angiotensin-converting enzyme 2 triggers viral entry, but other proteins may participate, including the neuropilin-1 receptor (NRP-1). Because both spike protein and vascular endothelial growth factor-A (VEGF-A)—a pronociceptive and angiogenic factor, bind NRP-1, we tested whether spike could block VEGF-A/NRP-1 signaling. VEGF-A-triggered sensory neuron firing was blocked by spike protein and NRP-1 inhibitor EG00229. Pronociceptive behaviors of VEGF-A were similarly blocked through suppression of spontaneous spinal synaptic activity and reduction of electrogenic currents in sensory neurons. Remarkably, preventing VEGF-A/NRP-1 signaling was antiallodynic in a neuropathic pain model. A "silencing" of pain through subversion of VEGF-A/NRP-1 signaling may underlie increased disease transmission in asymptomatic individuals. Abstract : Supplemental Digital Content is Available in the Text.Severe acute respiratory syndrome coronavirus 2's spike protein promotes analgesia by interfering with vascular endothelial growth factor-A/NRP1 pathway, which may affect disease transmission dynamics.